PENGARUH KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK BADAN PADA KANTOR PELAYANAN PAJAK PRATAMA LUBUK PAKAM - Suhaila Husna Samosir (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2020)
This study aims to find out, analyze and empirically prove the Service Quality of the Compliance of Corporate Taxpayers at the Lubuk Pakam Tax Service Office. The population of this study is the taxpayers registered in the Pratama Lubuk Pakam Tax Office totaling 8.235 taxpayers spread across 22 sub-districts in Deli Serdang Regency. The sampling technique used was proportional random sampling by distributing questionnaires, and respondents who returned the questionnaire were 99 corporate taxpayers. Testing the research data using simple linear regression analysis, partial tests and determinants. The results of this study indicate that Service Quality partially proved to influence the Compliance of Corporate Taxpayers at the Lubuk Pakam Primary Tax Service Office.